"Whenever you need support, you first turn to the group": motivations and functions of WhatsApp groups for youth living with HIV. Issue 3 (4th March 2023) - Healy, Elise; O'Malley, Gabrielle; Mugo, Cyrus; Kaggiah, Anne; Seeh, David; Muriithi, Alex; Lopez, Alana R.; Kumar, Manasi; Guthrie, Brandon; Moreno, Megan; John-Stewart, Grace; Inwani, Irene; et al.
ABSTRACT: Social support is a critical component of achieving positive health outcomes for youth living with HIV (YLWH). Mobile health (mHealth) has significant potential for providing social support to YLWH. However, little is known about the domains of social support most needed by YLWH which mHealth interventions might address. Drawing on the spontaneous creation of WhatsApp support groups by YLWH in Nairobi, Kenya, we characterized Kenyan YLWH's social support needs and potential roles of social media groups in meeting them. We conducted interviews and focus-groups with 68 YLWH, 24 caregivers and 20 healthcare workers, and observed two YLWH-led WhatsApp groups for 6 weeks. Youth reported that existing support systems, including family and healthcare workers, already provided informational and instrumental support. However, they emphasized unmet companionship and emotional support needs, leading to isolation, hopelessness, and medication adherence challenges. Participants identified connection with other YLWH as a unique source of emotional and companionship support that allowed them to feel more secure and less isolated. Interviews and observed WhatsApp chats demonstrated that WhatsApp groups were a desirable medium for companionship support that overcame barriers to in-person connection.